Exome sequencing expands the mechanism of SOX5‐associated intellectual disability: A case presentation with review of sox‐related disorders. (25th June 2015) - Nesbitt, Addie; Bhoj, Elizabeth J.; McDonald Gibson, Kristin; Yu, Zhenming; Denenberg, Elizabeth; Sarmady, Mahdi; Tischler, Tanya; Cao, Kajia; Dubbs, Holly; Zackai, Elaine H.; Santani, Avni
<x xml:space="preserve">Abstract</x> The SOX5 haploinsufficiency syndrome is characterized by global developmental delay, intellectual disability, language and motor impairment, and distinct facial features. The smallest deletion encompassed only one gene, SOX5 (OMIM 604975), indicating that haploinsufficiency of SOX5 contributes to neuro developmental delay. Although multiple deletions of the SOX5 gene have been reported in patients, none are strictly intragenic point mutations. Here, we report the identification of a de novo loss of function variant in SOX5 identified through whole exome sequencing. The proband presented with moderate developmental delay, bilateral optic atrophy, mildly dysmorphic features, and scoliosis, which correlates with the previously‐described SOX5‐associated phenotype. These results broaden the diagnostic spectrum of SOX5‐related intellectual disability. Furthermore it highlights the utility of exome sequencing in establishing an etiological basis in clinically and genetically heterogeneous conditions such as intellectual disability. © 2015 Wiley Periodicals, Inc.